Association between type 1 diabetes mellitus and dental caries: A systematic review and meta-analysis - Mahmoud Nassar; Omar Nassar; Hazem Abosheaishaa; Nahla Elhakim (Elsevier, 2024)
Objective: To assess the correlation between patients with type 1 diabetes mellitus (T1DM) and dental caries outcomes, including missing teeth, missing surface, filling teeth, filling surface, plaque index, gingival index, and calculus index. Methods: A comprehensive search was performed across EMBASE, Medline/Pubmed, and Web of Science databases from inception until February 20, 2023. Observational and interventional studies reporting dental caries outcomes in patients with T1DM were included. A random effects meta-analysis was performed to estimate the pooled effect sizes and 95 % confidence intervals. Results: Thirty-three studies met the criteria for inclusion in the meta-analysis, which revealed that patients with T1DM had a reduced risk of missing teeth in comparison to those without diabetes (control group), with a mean difference (MD) of -0.03, CI 95 % [-0.03, -0.03]. No significant differences were found in missing surface, filling teeth, filling surface, or calculus index between T1DM and non-diabetic groups. However, patients with T1DM had a significantly higher plaque index (MD: 0.47, CI 95 % [0.06, 0.89]) than the non-diabetic group. The overall MD in DFMT between the DM and non-DM groups was 0.47 (95 % CI: 0.13, 0.82). The gingival index showed no significant difference between the groups. Conclusion: This meta-analysis suggests that patients with T1DM have a higher plaque index than the non-diabetic group, whereas no significant differences were observed in other dental caries outcomes. Because of the considerable variability identified in certain analyses, additional research employing more extensive sample sizes and rigorous methodologies is required to validate these results.